What are refugees represented to be?: A frame analysis of the Presidential Regulation No. 125 of 2016 concerning the Treatment of Refugees "from abroad" - Sadjad, Mahardhika Sjamsoe’oed (Asian journal of law and society, 2021)
The Presidential Regulation No. 125 of 2016 concerning the Treatment of Refugees (PR) was a promising step to a better humanitarian response for refugees and asylum seekers arriving in Indonesia. It also provided a much-needed legal framework to validate refugees' presence and to ground civil - society organizations' advocacy on their behalf. However, a closer look at the PR and earlier drafts of the document shows serious compromises that: (1) reproduce the notion that refugees are only transiting in Indonesia; (2) frame refugees as passive objects, failing to recognize them as subjects with rights; and (3) prioritize security concerns that position refugees at odds with Indonesian society ('masyarakat'). Using the "What's the Problem Represented to be" approach, this article highlights what is included and excluded from the PR and how it falls short of guaranteeing meaningful protection for refugees while living in Indonesia.